2004
DOI: 10.1002/etep.16
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the rear‐face temperature of metals struck by lightning long‐duration currents

Abstract: SUMMARYThis paper presents an experimental investigation of the rear-face temperature rise of different metals struck by lightning long-duration currents on the front face. The experimental investigation simulates the heating effect of one current component of the natural lightning flashes that may strike in-flight or landed aircraft and rockets; munitions and nuclear weapons; and storage/collection tanks and pipelines of the petroleum/gas industries. In the case of a lightning strike the rear-face temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In this paper a computation of the three-dimension (3-D) transient temperature distribution in metals and composites struck by different lightning currents is introduced using a written computer program based on the finite volume technique. Also, the theoretical results are verified using the previously published experimental works [14,15].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this paper a computation of the three-dimension (3-D) transient temperature distribution in metals and composites struck by different lightning currents is introduced using a written computer program based on the finite volume technique. Also, the theoretical results are verified using the previously published experimental works [14,15].…”
Section: Introductionmentioning
confidence: 71%
“…Fig. 2 shows a comparison between the measured [14] and computed rear-face temperature contour maps ϑ r (x, y) for normal steel [19] at different times due to an LDC (square-like) current with an amplitude I = −93 A and a duration t = 325 ms. A good agreement is found between the measured and the computed ϑ r (x, y) during heating and cooling, too. Since the major part of the absorbed energy by the sample is transferred by heat conduction to the sample rear-face.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameter are associated with the appearance of hot spots in the metallic structure of the tanks, of induced voltages and with melting phenomena, as shown by specific numerical models and experimental tests (e.g. [10,11]). …”
Section: Introductionmentioning
confidence: 95%
“…Equation (6) uses this assumption and leads to an overestimate of the melted volume: Basically, the charge to be considered is the sum of the charge of the return stroke and the lightning continuing current. Laboratory experience has revealed that the effects of the return stroke charge may be of minor importance when compared to the effects of the continuing current [11].…”
Section: Damage Calculationmentioning
confidence: 99%